Purification, characterization, and specificity determination of a new serine protease secreted by penicillium waksmanii - Graminho, Eduardo Rezende; Da Silva, Ronivaldo Rodrigues [UNESP]; De Freitas Cabral, Tatiana Pereira; Arantes, Eliane Candiani; Da Rosa, Nathalia Gonsales; Juliano, Luiz; Okamoto, Debora Noma; De Oliveira, Lilian Caroline Gonçalves; Kondo, Marcia Yuri; Juliano, Maria Aparecida; Cabral, Hamilton (Springer Nature, 2013)
The purpose of this work was to purify a protease from Penicillium waksmanii and to determine its biochemical characteristics and specificity. The extracellular protease isolated that was produced by P. waksmanii is a serine protease that is essential for the reproduction and growth of the fungus. The protease isolated showed 32 kDa, and has optimal activity at pH 8.0 and 35 C towards the substrate Abz-KLRSSKQ-EDDnp. The protease is active in the presence of CaCl2, KCl, and BaCl, and partially inhibited by CuCl2, CoCl2 and totally inhibited by AlCl3 and LiCl. In the presence of 1 M urea, the protease remains 50 % active. The activity of the protease increases 60 % when it is exposed to 0.4 % nonionic surfactant-Triton X-100 and loses 10 % activity in the presence of 0.4 % Tween-80. Using fluorescence resonance energy transfer analysis, the protease showed the most specificity for the peptide Abz-KIRSSKQ-EDDnp with k cat/K m of 10,666 mM-1 s-1, followed by the peptide Abz-GLRSSKQ-EDDnp with a k cat/K m of 7,500 mM -1 s-1. Basic and acidic side chain-containing amino acids performed best at subsite S1. Subsites S2, S3, S′ 2, and S′ 1, S ′ 3 showed a preference for binding for amino acids with hydrophobic and basic amino acid side chain, respectively. High values of k cat/K m were observed for the subsites S2, S3, and S′ 2. The sequence of the N-terminus (ANVVQSNVPSWGLARLSSKKTGTTDYTYD) showed high similarity to the fungi Penicillium citrinum and Penicillium chrysogenum, with 89 % of identity at the amino acid level. © 2012 Springer Science+Business Media New York.
Keywords: Fungal enzymes; N-terminal Penicillium; Protease; Purification; Specificity; Biochemical characteristics; Extracellular protease; Fluorescence resonance energy transfer analysis; N-terminals; Nonionic; Optimal activity; Penicillium chrysogenum; Penicillium citrinum; Serine protease; Side-chains; Subsites; Tween 80; Calcium chloride; Copper compounds; Energy transfer; Enzyme activity; Nonionic surfactants; Peptides; Urea; Amino acids; aluminum chloride; barium chloride; calcium chloride; cobalt chloride; copper chloride; fungal enzyme; polysorbate 80; potassium chloride; serine proteinase; triton x 100; urea; amino acid sequence; amino terminal sequence; binding site; controlled study; enzyme activity; enzyme analysis; enzyme inhibition; enzyme kinetics; enzyme purification; enzyme release; enzyme specificity; enzyme substrate; enzyme synthesis; fluorescence resonance energy transfer; fungal reproduction; fungus growth; nonhuman; Penicillium; Penicillium waksmanii; pH; protein cleavage; protein function; species difference; Amino Acid Sequence; Enzyme Stability; Extracellular Space; Fungal Proteins; Kinetics; Molecular Sequence Data; Protein Transport; Serine Proteases; Substrate Specificity; Fungi